A Development of Futsal Court Booking System - Suhaimi, Ahmad Naim Shafiq; Sahid, Mohd Zanes (Applied Information Technology And Computer Science, 2023)
The Futsal Court Booking System was develop to increase the efficiency of the existing court booking process which still uses the manual method at the Indera Mahkota Futsal Court Center. Based on the existing system, all booking data, staff profiles etc. are stored manually in a log book which can lead to data loss and also difficult to handle. This booking system is able to display a list of customer scheduling so that users can see the availability easily and concisely. So, the system is also developed for all bookings and other data so that it can be stored in a database that will be more easily managed electronically. System development is based on prototype methodology. This system provides 6 functional modules such as registration and login module, court booking module, court information management module, payment module, notification module and report module. PhP and MySql are used as programming and database systems. This system helps Kuantan residents in particular to book futsal courts in an easier and more flexible way.